Comparative evaluation of the effects of Beclomethasone and Adcortyle in the treatment of oral lichen planus - Sedigheh Azimi; Nasrin Rafieian; Hamid Reza Abdolsamadi (Isfahan University of Medical Sciences, 2011)
Introduction: Oral lichen planus (OLP) is a chronic inflammatory disease with an unknown etiology. One of the most acceptable techniques to control OLP is the use of topical steroids. One of the most commonly used drugs to control of OLP lesions is Acortyle. On the other hand, Beclomethasone is a local corticosteroid which can easily be used in the oral cavity. The aim of this study was to compare the effects of these drugs in controlling OLP.Materials and Methods: This single-blind clinical trial was carried out on 19 patients (males=6, females=13, mean age=53) at Shahid Beheshti University of Medical Sciences in 2009-10. Beclomethasone spray and Adcortyle paste were simultaneously used in bilateral lesions (on buccal mucosa, gingiva or lateral aspect of the tongue) for a period of 3‒6 weeks and then tapered. Drugs effect was evaluated by "VAS", Kaliakatsoau classification and REU. Data were collected and analyzed using paired t-test and Wilcoxon's and Kolmogorov-Smirnov tests.Results: There was no significant different between the efficacy of the two drugs in decreasing lesions' surface areas and lowering pain intensity after 3 weeks (p value = 0.042). Conclusion: The results of this study showed that the two corticosteroids are both effective in the clinical management of OLP. Acortyle was somewhat more efficacious than Beclomethasone in reducing pain and burning sensation, with no statistically significant differences. On the other hand, the patients were more cooperative with the use of Beclomethasone because it is easier to use sprays compared to pastes. Key words: Beclomethasone, Local corticosteroids, Oral lichen planus, Triamcinolone acetonide.